Zircon Lu–Hf isotopic compositions of metaluminous and peralkaline A-type granitic plutons of the Emeishan large igneous province (SW China): Constraints on the mantle source - Gregory Shellnutt, J.; Wang, Christina Yan; Zhou, Mei-Fu; Yang, Yueheng (Journal of Asian earth sciences, 2009)
Permian A-type granitoids of the Emeishan large igneous province (ELIP) in the Panxi region, SW China, are predominantly peralkaline and metaluminous in composition. In situ zircon Hf isotopic compositions along with whole rock trace element and Nd isotopic data are used to examine the probable source characteristics of these A-type granitic plutons. Zircons from the Baima and Taihe peralkaline plutons have weighted average εHf (T) values of +8.7 ± 0.4 and +9.2 ± 1.0, whereas the Woshui and Huangcao metaluminous plutons have differing εHf (T) values (+8.6 ± 0.2 and +5.8 ± 0.3, respectively). Previous studies have suggested that the plutons were derived by differentiation (e.g. fractionation or partial melting) of mafic magmas from an enriched mantle source similar to oceanic island basalt with little or no contribution from the crust (εNd (T) = +1.3 to +3.2, Zr/Nb = 0.9–14.4, Rb/Nb = 0.1–8.4 and Th/Ta = <4.0). Therefore, we interpret the Hf isotopic data of the Baima, Taihe, Woshui and Huangcao plutons to be indicative of the Emeishan mantle plume. The similar zircon εHf (T) values of the Woshui and Baima plutons indicates that spatially and temporally associated peralkaline and metaluminous A-type granitic rocks can originate from the same mantle source without crustal assimilation.